Low-loss iron-based nanocrystalline powder core and preparation method thereof
By pulverizing, atomizing, mechanical ball milling, passivation treatment and coating of the iron-based amorphous master alloy, low-loss iron-based nanocrystalline powder core is prepared, and the magnetic loss of the iron-based nanocrystalline powder core in the prior art is solved. High problem achieves high frequency and high efficiency magnetic performance.
Patent Information
- Application Number
- CN202411558859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing iron-based nanocrystalline powder cores have high magnetic losses in high frequency and high efficiency applications, which are difficult to meet the needs of miniaturization and high frequency.
通过将铁基非晶母合金加热熔融后粉碎雾化,并进行机械球磨,得到均匀的片状铁基纳米晶粉。 Then passivation treatment and coating are carried out, including processing in the acid solution and passing a mixed gas of carbon dioxide, oxygen and nitrogen, adding a polyamide resin acetone solution for coating, and finally obtaining low-loss iron-based nanocrystals through crystallization annealing Powder core.
It realizes low magnetic loss and high effective magnetic permeability of iron-based nanocrystalline powder core, reduces eddy current loss, and improves the uniform distribution of magnetic flux, and is suitable for high frequency and high efficiency electronic components.
Smart Images

Figure BDA0005117329590000071 
Figure BDA0005117329590000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of iron-based nanocrystalline powder cores, and in particular to a low-loss iron-based nanocrystalline powder core and a preparation method thereof. Background Art
[0002] As an important functional material, magnetic materials are widely used in electronics, communications, computers, medical and other fields. Among them, iron-based nanocrystalline powder cores have attracted much attention due to their excellent magnetic properties such as excellent magnetic permeability, low hysteresis loss, high thermal stability, and similar plastic processing properties to other metals.
[0003] As basic electronic components develop towards miniaturization, higher frequency and higher efficiency, amorphous and nanocrystalline magnetic powders need to have lower core magnetic losses and higher effective magnetic permeability; therefore, developing a nanocrystalline powder core with excellent performance has become one of the current research hotspots in nanocrystalline powder core materials. Summary of the invention
[0004] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a low-loss iron-based nanocrystalline powder core and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing a low-loss iron-based nanocrystalline powder core comprises the following steps:
[0007] S1: heating and melting the iron-based amorphous master alloy, crushing and atomizing it, and then ball milling it to obtain uniform flaky iron-based nanocrystalline powder;
[0008] S2: passivating the iron-based nanocrystalline powder and then coating it to obtain a pretreated material;
[0009] The details are as follows:
[0010] Firstly, the iron-based nanocrystalline powder is treated in an acid solution, and a mixed gas of carbon dioxide, oxygen and nitrogen is introduced during the treatment, and then a polyamide resin acetone solution is added for coating;
[0011] S3: Pressing the pretreated material into a shape, performing crystallization annealing, and obtaining an iron-based nanocrystalline powder core.
[0012] As a preferred embodiment of the present invention, the volume ratio of the mixed gas of carbon dioxide, oxygen and nitrogen is 1-3:0.5-2:4-8.
[0013] As a preferred embodiment of the present invention, the crystallization annealing is specifically:
[0014] The vacuum heat treatment process is adopted: under nitrogen atmosphere, the heating rate is 0.5-1℃ / min, the annealing temperature is 500-600℃, the annealing time is 40-60min, the furnace is air-cooled to 180-200℃, and then naturally cooled to room temperature.
[0015] As a preferred embodiment of the present invention, colloidal silica is also added to the acid solution.
[0016] As a preferred embodiment of the present invention, the acid solution is phosphoric acid or nitric acid.
[0017] As a preferred embodiment of the present invention, in step S2, micro-nano hybrid particles are added to the polyamide resin acetone solution, and the nano-hybrid comprises nano-lithium magnesium silicate and micron vermiculite.
[0018] As a preferred embodiment of the present invention, the mass ratio of the nano-lithium magnesium silicate to the micron vermiculite is 1:3-5.
[0019] As a preferred embodiment of the present invention, the micron vermiculite is a mixture obtained by processing at different temperatures.
[0020] As a preferred embodiment of the present invention, the different temperatures are 300-500°C, 500-700°C, and 700-1000°C respectively.
[0021] The invention also discloses a low-loss iron-based nanocrystalline powder core, which is prepared by any of the above preparation methods.
[0022] The beneficial effects of the present invention are:
[0023] (1) A low-loss iron-based nanocrystalline powder core of the present invention is prepared by first melting an iron-based amorphous master alloy and then crushing and atomizing it to obtain spherical iron-based nanocrystalline powder, and then mechanically ball-milling it to obtain uniform flaky iron-based nanocrystalline powder, so that the powder particle size is more uniform, which is more conducive to the subsequent passivation coating crystallization and pressing molding. The magnetic powder core with a relatively uniform particle size can reduce the gaps and irregularities between particles, making the distribution of magnetic flux in the magnetic powder core more uniform, thereby reducing eddy current loss.
[0024] (2) The present invention passivates iron-based nanocrystalline powder with phosphoric acid to form a phosphating film on the surface of the powder. At the same time, a mixed gas of carbon dioxide and oxygen is introduced. On the one hand, carbon dioxide can effectively adjust the pH of phosphoric acid. On the other hand, the introduction of oxygen can react with the phosphating film to obtain a phosphating film with good antioxidant properties, thereby improving the passivation effect on the powder. Furthermore, nitrogen can dilute the concentration of carbon dioxide and oxygen, and can also control the integrity of the passivation degree of the magnetic powder, thereby improving the completeness of the passivation of the powder, that is, the integrity of the phosphating film.
[0025] (3) The silica colloid added in the passivation process of the present invention, on the one hand, makes the phosphating film free of gaps and more compact, and at the same time, micro-nano mixed particles are added to the polyamide resin acetone solution. Since lithium magnesium silicate has a special layered structure and vermiculite treated at different temperatures has different thermal adsorption spaces, combined with the combination of micro-nano sizes, it can adsorb an insulating film containing a special structure that responds to temperature and heat on the surface of the nanocrystalline powder. Combined with a specific crystallization annealing process, it can make the nanocrystalline powder precipitate more α-Fe grains and inhibit the precipitation of non-magnetic grains. DETAILED DESCRIPTION
[0026] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0027] The composition of the iron-based amorphous master alloy is Fe 80.5 Si 0.5 B 10.5 P5 0.5 C2 Ni1.
[0028] In the following embodiments, the pulverization atomization specifically includes two steps: gas atomization and high-speed rotary disk centrifugal atomization. In the gas atomization process, the atomization pressure is 3 MPa; in the high-speed rotary disk centrifugal atomization process, the rotation speed of the high-speed rotary disk is 18000 r / min.
[0029] Example 1
[0030] A method for preparing a low-loss iron-based nanocrystalline powder core comprises the following steps:
[0031] S1: heating and melting the iron-based amorphous master alloy, crushing and atomizing it, and then ball milling it to obtain uniform flaky iron-based nanocrystalline powder;
[0032] S2: passivating the iron-based nanocrystalline powder and then coating it to obtain a pretreated material;
[0033] The details are as follows:
[0034] Firstly, the iron-based nanocrystalline powder is treated in an acid solution, and a mixed gas of carbon dioxide, oxygen and nitrogen is introduced during the treatment, and then a polyamide resin acetone solution is added for coating;
[0035] S3: Pressing the pretreated material into a shape, performing crystallization annealing, and obtaining an iron-based nanocrystalline powder core.
[0036] The volume ratio of the mixed gas of carbon dioxide, oxygen and nitrogen is 3:2:8.
[0037] The crystallization annealing is specifically as follows:
[0038] A vacuum heat treatment process was used: under a nitrogen atmosphere, the heating rate was 1°C / min, the annealing temperature was 550°C, the annealing time was 50min, the furnace was air-cooled to 190°C, and then naturally cooled to room temperature.
[0039] The acid solution is also added with silica colloid accounting for 3 wt % of the acid solution mass.
[0040] The acid solution is phosphoric acid.
[0041] In step S2, micro-nano hybrid particles accounting for 5 wt% of the polyamide resin acetone solution are added to the polyamide resin acetone solution, wherein the nano-hybrid comprises nano-lithium magnesium silicate and micron vermiculite.
[0042] The mass ratio of the nano-lithium magnesium silicate to the micron vermiculite is 1:3.
[0043] The micron vermiculite is a mixture obtained by processing at different temperatures.
[0044] The different temperatures are 300° C., 600° C., and 900° C., respectively, and each temperature section is treated for 2 hours.
[0045] Example 2
[0046] A method for preparing a low-loss iron-based nanocrystalline powder core comprises the following steps:
[0047] S1: heating and melting the iron-based amorphous master alloy, crushing and atomizing it, and then ball milling it to obtain uniform flaky iron-based nanocrystalline powder;
[0048] S2: passivating the iron-based nanocrystalline powder and then coating it to obtain a pretreated material;
[0049] The details are as follows:
[0050] Firstly, the iron-based nanocrystalline powder is treated in an acid solution, and a mixed gas of carbon dioxide, oxygen and nitrogen is introduced during the treatment, and then a polyamide resin acetone solution is added for coating;
[0051] S3: Pressing the pretreated material into a shape, performing crystallization annealing, and obtaining an iron-based nanocrystalline powder core.
[0052] The volume ratio of the mixed gas of carbon dioxide, oxygen and nitrogen is 2:1:7.
[0053] The crystallization annealing is specifically as follows:
[0054] A vacuum heat treatment process was used: under a nitrogen atmosphere, the heating rate was 0.9°C / min, the annealing temperature was 550°C, the annealing time was 50min, the furnace was air-cooled to 200°C, and then naturally cooled to room temperature.
[0055] The acid solution is also added with silica colloid accounting for 3 wt % of the acid solution mass.
[0056] The acid solution is phosphoric acid.
[0057] In step S2, micro-nano hybrid particles accounting for 5 wt% of the polyamide resin acetone solution are added to the polyamide resin acetone solution, wherein the nano-hybrid comprises nano-lithium magnesium silicate and micron vermiculite.
[0058] The mass ratio of the nano-lithium magnesium silicate to the micron vermiculite is 1:4.
[0059] The micron vermiculite is a mixture obtained by processing at different temperatures.
[0060] The different temperatures are 400° C., 600° C., and 900° C., respectively, and each temperature section is treated for 2 hours.
[0061] Example 3
[0062] A method for preparing a low-loss iron-based nanocrystalline powder core comprises the following steps:
[0063] S1: heating and melting the iron-based amorphous master alloy, crushing and atomizing it, and then ball milling it to obtain uniform flaky iron-based nanocrystalline powder;
[0064] S2: passivating the iron-based nanocrystalline powder and then coating it to obtain a pretreated material;
[0065] The details are as follows:
[0066] Firstly, the iron-based nanocrystalline powder is treated in an acid solution, and a mixed gas of carbon dioxide, oxygen and nitrogen is introduced during the treatment, and then a polyamide resin acetone solution is added for coating;
[0067] S3: Pressing the pretreated material into a shape, performing crystallization annealing, and obtaining an iron-based nanocrystalline powder core.
[0068] The volume ratio of the mixed gas of carbon dioxide, oxygen and nitrogen is 3:1:8.
[0069] The crystallization annealing is specifically as follows:
[0070] A vacuum heat treatment process was used: under a nitrogen atmosphere, the heating rate was 1°C / min, the annealing temperature was 600°C, the annealing time was 60min, the furnace was air-cooled to 200°C, and then naturally cooled to room temperature.
[0071] The acid solution is also added with silica colloid accounting for 3 wt % of the acid solution mass.
[0072] The acid solution is phosphoric acid or nitric acid.
[0073] In step S2, micro-nano hybrid particles accounting for 5 wt% of the polyamide resin acetone solution are added to the polyamide resin acetone solution, wherein the nano-hybrid comprises nano-lithium magnesium silicate and micron vermiculite.
[0074] The mass ratio of the nano-lithium magnesium silicate to the micron vermiculite is 1:5.
[0075] The micron vermiculite is a mixture obtained by processing at different temperatures.
[0076] The different temperatures are 400° C., 600° C., and 1000° C., respectively, and each temperature section is treated for 2 hours.
[0077] Comparative Example 1
[0078] The difference from Example 1 is that there is no crushing and atomization step, and the rest is the same as Example 1.
[0079] Comparative Example 2
[0080] The difference from Example 1 is that in step S2, no mixed gas is introduced, and the rest is the same as Example 1.
[0081] Comparative Example 3
[0082] The difference from Example 1 is that in step S2, no carbon dioxide is introduced into the mixed gas. The rest is the same as Example 1.
[0083] Comparative Example 4
[0084] The difference from Example 1 is that in step S2, no silica colloidal body is added to the acid solution, and the rest is the same as Example 1.
[0085] Comparative Example 5
[0086] The difference from Example 1 is that no micro-nano hybrid particles are added to the polyamide resin acetone solution. The rest is the same as Example 1.
[0087] The performance of the above embodiments and comparative examples were tested, and the test results are shown in Table 1. Specifically, the magnetic permeability of the crystal powder core at a frequency of 1 MHz and the loss at 200 kHz and 0.05 T were tested.
[0088] Table 1 Performance test results of embodiments and comparative examples
[0089]
[0090]
[0091] It can be seen from the above table that the performance of the embodiment is better than that of the comparative example, and the main reasons may be as follows: From the analysis of comparative example 1, it can be seen that the embodiment first obtains spherical iron-based nanocrystalline powder by melting the iron-based amorphous master alloy and then crushing and atomizing it, and then mechanically ball-milling is performed to obtain uniform flaky iron-based nanocrystalline powder, so that the powder particle size is more uniform, which is more conducive to the subsequent passivation coating crystallization and more conducive to compression molding. The magnetic powder core with a relatively uniform particle size can reduce the gaps and irregularities between the particles, and make the distribution of the magnetic flux in the magnetic powder core more uniform, thereby reducing eddy current losses; From the analysis of comparative examples 2 and 3, it can be seen that a phosphating film is formed on the surface of the crystal powder, and a mixed gas of carbon dioxide and oxygen is introduced at the same time. On the one hand, carbon dioxide can effectively adjust the pH of phosphoric acid, and on the other hand, the introduction of oxygen can react with the phosphating film to obtain an anti- The phosphating film with good oxidation performance improves the passivation effect on the crystal powder. Furthermore, nitrogen can dilute the concentration of carbon dioxide and oxygen, and can also control the integrity of the passivation degree of the magnetic powder, thereby improving the completeness of the passivation of the crystal powder, that is, the integrity of the phosphating film. Comparative Examples 4 and 5 show that the silica colloid added in the passivation process of the embodiment makes the phosphating film free of gaps and more compact. At the same time, micro-nano mixed particles are added to the polyamide resin acetone solution. Since lithium magnesium silicate has a special layered structure, and vermiculite treated at different temperatures has different thermal adsorption spaces, combined with the matching of micro-nano sizes, an insulating film containing a special response structure to temperature and heat is adsorbed on the surface of the nanocrystalline powder. Combined with a specific crystallization annealing process, more α-Fe grains can be precipitated from the nanocrystalline powder, and the precipitation of non-magnetic grains can be suppressed.
[0092] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all these changes and deformations should fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a low-loss iron-based nanocrystalline powder core, characterized in that: The following steps are involved: S1: heating and melting the iron-based amorphous master alloy, crushing and atomizing it, and then ball milling it to obtain uniform flaky iron-based nanocrystalline powder; S2: passivating the iron-based nanocrystalline powder and then coating it to obtain a pretreated material; The details are as follows: Firstly, the iron-based nanocrystalline powder is treated in an acid solution, and a mixed gas of carbon dioxide, oxygen and nitrogen is introduced during the treatment, and then a polyamide resin acetone solution is added for coating; S3: Pressing the pretreated material into a shape, performing crystallization annealing, and obtaining an iron-based nanocrystalline powder core.
2. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 1, characterized in that: The volume ratio of the mixed gas of carbon dioxide, oxygen and nitrogen is 1-3:0.5-2:4-8.
3. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 1, characterized in that: The crystallization annealing is specifically: The vacuum heat treatment process is adopted: under nitrogen atmosphere, the heating rate is 0.5-1℃ / min, the annealing temperature is 500-600℃, the annealing time is 40-60min, the furnace is air-cooled to 180-200℃, and then naturally cooled to room temperature.
4. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 1, characterized in that: Colloid dioxide is also added into the acid solution.
5. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 1, characterized in that: The acid solution is phosphoric acid or nitric acid.
6. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 1, characterized in that: In step S2, micro-nano hybrid particles are added to the polyamide resin acetone solution, wherein the nano-hybrid comprises nano-lithium magnesium silicate and micron vermiculite.
7. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 5, characterized in that: The mass ratio of the nano-lithium magnesium silicate to the micron vermiculite is 1:3-5.
8. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 5, characterized in that: The micron vermiculite is a mixture obtained by processing at different temperatures.
9. The method for preparing a low-loss iron-based nanocrystalline powder core according to claim 8, characterized in that: The different temperatures are 300-500°C, 500-700°C, and 700-1000°C respectively.
10. A low-loss iron-based nanocrystalline powder core, characterized in that: The method is prepared by any one of claims 1 to 9.